2010
DOI: 10.1002/jgm.1445
|View full text |Cite
|
Sign up to set email alerts
|

GP96 C‐terminal improves Her2/neu DNA vaccine

Abstract: The C-terminal of GP96 has potent adjuvant activity in eliciting a significant immune response when fused with Her2/neu. It may be used as molecular adjuvant along with other tumor or bacterial/viral antigens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 73 publications
1
13
0
Order By: Relevance
“…In this article, the result on the efficiency of C-terminally fusion of gp96 Cterminal to TM+ECD of rat Her2/neu DNA vaccine is presented. It is noteworthy to remind that this study was conducted at the same time of the previous report (Pakravan et al 2010a). The results of N-terminally fusion of gp96 Cterminal to TM+ECD of rat Her2/neu were published previously (Pakravan et al 2010a) and statistical analysis with C-terminally fusion of gp96 C-terminal to TM+ECD of rat Her2/neu have been mentioned here for comparison.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…In this article, the result on the efficiency of C-terminally fusion of gp96 Cterminal to TM+ECD of rat Her2/neu DNA vaccine is presented. It is noteworthy to remind that this study was conducted at the same time of the previous report (Pakravan et al 2010a). The results of N-terminally fusion of gp96 Cterminal to TM+ECD of rat Her2/neu were published previously (Pakravan et al 2010a) and statistical analysis with C-terminally fusion of gp96 C-terminal to TM+ECD of rat Her2/neu have been mentioned here for comparison.…”
Section: Introductionmentioning
confidence: 84%
“…NM_003299) was cloned into pHer2, downstream of Her2/neu (pHer2/CT). Preparation of pCT/Her2 was described previously (Pakravan et al 2010a). The expression of each construct was evaluated by cloning of green fluorescent gene at the end of gene, as described previously (Pakravan et al 2010c).…”
Section: Dna Expression Vectors and Vaccinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have shown the adjuvant activity of the N-/C-terminal domains of gp96 in DNA or protein vaccine strategies. For instance, fusion of the C-terminal domain to Her2/neu inhibited the tumor growth (Pakravan et al, 2010). Moreover, the N-terminal domain has also potent adjuvant activity toward hepatitis B surface antigen (Yan et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the C-terminal of gp96 can be used as molecular adjuvant along with other tumor/ bacterial/viral antigens for improving vaccine potency. 52 Furthermore, our research group applied two strategies including linkage of immune-stimulatory molecules (N-terminal of gp96), accompanied with PEI600-Tat as non-viral gene delivery system to evaluate DNA vaccine efficacy against HPV infections. It was found that immunization with E7-NT (gp96) fusion gene led to increase IFN-γ level as compared with E7 alone.…”
Section: Dna-based Vaccinesmentioning
confidence: 99%